Microsoft office excel macro-based information system application training for travel entrepreneurs in Samarinda - Ratna Wulaningrum; Ibrahim MS; Tumanggor Clinsman Andromeda (Community Empowerment, 2021)
This community service aims to improve the understanding and skills of travel entrepreneurs in Samarinda in using integrated information system applications with macro in excel. The problems faced by travel entrepreneurs are bookkeeping and financial management which are still conventional so that the majority of them cannot know for sure their financial position and assets. This community service is carried out with training that begins with a process of observation and discussion with travel entrepreneurs in Samarinda. Furthermore, the entrepreneurs were given material about the urgency of an information system based on Macro in Excel for business management. The results of the service activities reveal that travel entrepreneurs can practically use the macro in excel well, but still need to be careful in the data input process. Programs that have been created can be developed because the facilities available in macro is very customizable.